Acquired von Willebrand’s Syndrome Associated with Hydatid Disease of the Spleen – Disappearance after Splenectomy - Richard, C; Sedano, M C; Cuadrado, M A; Recio, M; Hermosa, V; Zubizarreta, A (Thrombosis and Haemostasis, 1984)
A new case of acquired von Willebrand’s syndrome (vWS) is described in a 31-year-old woman with a hydatid splenomegaly and with a history of repeated abortions at an advanced stage of pregnancy, a positive serology for syphilis and a mildly elevated titre of antinuclear antibodies, with no family history of bleeding.There is an inhibitory effect on factor VIII: C (antihaemophilic factor) as well as on factor VIIIR: Ag (related antigen) and on factor VIIIR:RCo (ristocetin cofactor), and it is precipitated by rabbit anti-IgG antiserum. This inhibitory effect was demonstrated using the patient’s plasma heated to 56° C for one hour so as to dissociate circulating immunocomplexes.All the abnormalities of haemostasis, as well as the positive serology for syphilis, disappeared after splenectomy, and the ANA titre reverted to normal.The clinical and biological peculiarities of the case are discussed, and are interpreted in the light of the findings recorded in patients showing “lupus” anticoagulant.
Keywords: Acquired von Willebrand’s syndrome; Auto-antibody